Market study for a production unit of natural flavors for yogurts: Part 1. Consumer and processor expectations - Orounladji Boko, Michel; Tankoano, Abel; Sib, Ollo; Vall, Eric (2024)
This market study aimed to determine the feasibility and potential of setting up a production unit for extracts based on local products (non-timber forest products, and various agricultural products) to flavor yogurts made from local milk in the Bobo Dioulasso dairy basin. More specifically, the project involved : Analyze demand from yogurt milk processors, Identify consumer preferences and expectations, Assess technical and logistical challenges, Analyze market opportunities. This report presents the study results relating to the two first abovementioned points.